2020
DOI: 10.1101/2020.03.06.980631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid mechanoenzymatic saccharification of lignocellulosic biomass without bulk water or chemical pre-treatment

Abstract: Lignocellulosic material is an abundant renewable resource with the potential to replace petroleum as a feedstock for the production of fuels and chemicals. The large scale deployment of biomass saccharification is, however, hampered by the necessity to use aggressive reagents and conditions, formation of side-products, and the difficulty to reach elevated monosaccharide concentrations in the crude product. Herein we report the high efficacy of Reactive Aging (or Raging, a technique where enzymatic reaction mi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…Using enzymes in moist-solid reaction mixtures rather than in traditional dilute solutions or slurries is an emergent strategy (36) that has proven beneficial for the breakdown of recalcitrant biopolymers such as cellulose (22,23), xylan (25), and chitin (26). Such reaction conditions provide a milieu that is closer to the natural setting of enzymes like HiC, which are secreted in the environment by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using enzymes in moist-solid reaction mixtures rather than in traditional dilute solutions or slurries is an emergent strategy (36) that has proven beneficial for the breakdown of recalcitrant biopolymers such as cellulose (22,23), xylan (25), and chitin (26). Such reaction conditions provide a milieu that is closer to the natural setting of enzymes like HiC, which are secreted in the environment by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Using enzymes in moist-solid reaction mixtures rather than in traditional dilute solutions is an emergent strategy(36) that has proven beneficial for the breakdown of recalcitrant biopolymers such as cellulose, (23,24) xylan, (25) and chitin (26). Such reaction conditions provide a milieu that is closer to the natural setting of enzymes like HiC, which are secreted in the environment by microorganisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports on the mechanoenzymatic breakdown of the biopolymers cellulose, (21,23,24) xylan (25), and chitin (26) demonstrated that enzyme kinetics under aging conditions are hyperbolic. These reactions can be accelerated by periodically repeating the milling process just before the yield reaches a plateau, in a process termed reactive aging (RAging).…”
Section: Acceleration Of Pet Hydrolysis By Reactive Aging (Raging)mentioning
confidence: 99%
“…While the pretreatment technology destroys the structure of lignocellulose and improves the enzymatic hydrolysis performance of raw materials, severe reaction conditions lead to a series of side reactions and produce a variety of complex compounds, mainly including furans, organic acids, and lignin derivatives [66][67][68][69]. All these substances have a complex shape and strongly inhibit the saccharification and fermentation processes, and these inhibitors must be removed, that is, the pretreated materials must be detoxified [46,62,70].…”
Section: Solution Of Raw Materials Pretreatmentmentioning
confidence: 99%